Schools, sexual violence, and safety: Adolescent girls and writing resistance at an afterschool program in suburban Mumbai. (3rd December 2019) - Bhattacharya, Usree; McGovern, Kathleen
Abstract : Two and a half million adolescent girls have experienced some form of sexual violence in India; significantly, they make up a quarter of all rape cases, despite being a small percentage of the population (Raj and McDougal, 2014). Parents and girls' fears about safety contributes to their high dropout rates within Indian education, but thus far there has been little research on this topic. Focusing on underprivileged adolescent girls at an afterschool site in Mumbai, India, this qualitative study investigates how within this landscape of sexual violence, writing serves as a medium to name, resist, and transform it. Specifically, we scrutinize the articulation of resistance which attempts to contest social norms, cultural conventions, and other forms of everyday hegemony. We examine data extracts from essays written by three adolescent girls participating in the afterschool program as part of a pilot study that took place in December 2016. The analysis of these extracts illuminates how the girls, through their writing, articulate their vulnerabilities about their own and others' personal safety. Furthermore, it reveals how it is connected to their ability to access education. Moreover, it highlights the ways in which the girls resist parental and other socio-cultural pressures. Finally, the analysis sheds light on the complex and powerful ways in which the girls assert their independence, demand autonomy over their lives, and exercise agency. Ultimately, this investigation offers a path forward for Indian educators to reimagine girls' education in light of girls' safety issues, using writing as a space to articulate a literacy of resistance and hope.